Educational Software Audit - Galimyanov, Anis F. (2019)
This article describes an audit in the IT field, namely the audit of software using the example of Kazan (Volga Region) Federal University. The most significant goal of the audit is to discover the full list of programs installed on the enterprise's machines. This list should include all software products without exception: both used by employees to solve their daily questions, and those programs that were not used at all, but simply downloaded for interest. It is noted, including incorrectly deleted software that has retained its fingerprints in the system. In the work, a comparison was made of the most well-known and used products of Microsoft System Center Configuration Manager and Kaspersky Security Center and a comparative integration of all the information that collects these funds was performed. Collecting and processing data on the software installed on the machines of an educational institution is a time-consuming task. The system of automated software audit connects remotely to computers on the local network and accumulates data about the software installed on them. To improve this process, a program with the necessary interface has been written, which allows obtaining a database that contains data about all computers with the software installed on them. This will further make it possible to formulate recommendations for the further development of the computer park on the example of KPU.